Analisis Positioning Fast Food Restaurant di Indonesia - Wulan Oktavia; Amelia Nur Fitri; Nurhasanah Nurhasanah (Departement of Mathematics Education, 2023)
This study aims to analyze the positioning of fast food restaurants in Indonesia. the number of samples collected was 60 respondents. The research instrument used in collecting data in this study was using a questionnaire filled out by respondents and a Likert scale. while for technical data analysis used is discriminant. The results of the study show that the positioning maps of fasfood brands A, B, C, and D are known to have different positions. The results of this study indicate that: (1) Attributes that are considered important by consumers. (2) Brand A is good in terms of Drive Thru (3) Brand B is good in terms of taste. (4) Brand C is good in terms of taste. (5) Brand D is good in both attributes that are considered important, namely Taste and Drive Thru, so it must maintain and improve the service quality and speed of Drive Thru and improve the taste so that it can be superior in the minds of consumers.